2020
DOI: 10.1186/s43054-020-00037-9
|View full text |Cite
|
Sign up to set email alerts
|

Practical approach to COVID-19: an Egyptian pediatric consensus

Abstract: Background: Outbreak of a novel corona virus was reported in China on December 2019. Sooner, a global spread was reported and WHO announced a public health emergency of international concern and then declared it as a pandemic. Egypt announced the first case on February 14, 2020, and since that time, cases are increasing. Main body: There is increasing need to simplify the practical approach for pediatricians and other health care workers in a step wise manner; how to deal with COVID-19 cases, how to care for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…According to WHO and NICE guidelines, patients with mild or moderate symptoms are not encouraged for antibiotic use unless showing signs of secondary bacterial pneumonia 10,15,21 . Therefore, COVID‐19 patients could be managed according to recommendation for antibiotic use of CAP guidelines, however, this widespread of azithromycin and other broad‐spectrum antibiotics is highly concerning and not supported by scientific evidence till now 22 .…”
Section: Discussionmentioning
confidence: 99%
“…According to WHO and NICE guidelines, patients with mild or moderate symptoms are not encouraged for antibiotic use unless showing signs of secondary bacterial pneumonia 10,15,21 . Therefore, COVID‐19 patients could be managed according to recommendation for antibiotic use of CAP guidelines, however, this widespread of azithromycin and other broad‐spectrum antibiotics is highly concerning and not supported by scientific evidence till now 22 .…”
Section: Discussionmentioning
confidence: 99%
“…According to this theory, the relatively low rates of COVID-19 infections and mortalities in Egypt may be partially attributed to the country's early intake of BCG vaccination ( Medhat and El Kassas, 2020 ). Mostafa et al (2020) found that breast milk samples from the COVID-19–positive mothers after the first lactation were negative for the virus. The authors stated that breastfeeding is effective against infectious diseases because it strengthens the immune system by transferring antibodies from the mother and other anti-infective factors; therefore, all confirmed or suspected COVID-19 mothers with any symptoms should follow standard infant feeding guidelines with appropriate precautions ( Breastfeeding Advice during the COVID-19 outbreak, n.d. ).…”
Section: Covid-19 Morbidity Mortality and Associated Risk Factors In Egyptmentioning
confidence: 97%
“…However, these percentages could be underestimated because COVID-19 infection causes many asymptomatic and subclinical cases. 23 Compared to other studies in Egypt, showing the incidence of HCWs infection was 2.37%, 11%, and 13.5% 10,26,27 respectively. Another cross-sectional study in New York City 23 reported a 19.4% infection rate.…”
Section: Discussionmentioning
confidence: 72%